Glial biology in learning and cognition - Fields, R Douglas; Araque, Alfonso; Johansen-Berg, Heidi; Lim, Soo-Siang; Lynch, Gary; Nave, Klaus-Armin; Nedergaard, Maiken; Perez, Ray; Sejnowski, Terrence; Wake, Hiroaki (The Neuroscientist (Baltimore, Md.), 2014)
Neurons are exquisitely specialized for rapid electrical transmission of signals, but some properties of glial cells, which do not communicate with electrical impulses, are well suited for participating in complex cognitive functions requiring broad spatial integration and long-term temporal regulation. Astrocytes, microglia, and oligodendrocytes all have biological properties that could influence learning and cognition. Myelination by oligodendrocytes increases conduction velocity, affecting spike timing and oscillations in neuronal activity. Astrocytes can modulate synaptic transmission and may couple multiple neurons and synapses into functional assemblies. Microglia can remove synapses in an activity-dependent manner altering neural networks. Incorporating glia into a bicellular mechanism of nervous system function may help answer long-standing questions concerning the cellular mechanisms of learning and cognition.